0

# how to solve each system by elimination -6x-6y=6 and -6x+3y=-12

i dont know how to do this
Thanks

### 2 Answers by Expert Tutors

Parviz F. | Mathematics professor at Community CollegesMathematics professor at Community Colle...
4.8 4.8 (4 lesson ratings) (4)
0
-6X - 6Y = 6
-6X  +3Y = -12

Simplify both equations:

X + Y = -1
2X - Y = 4
3X = 3
X =1

Y =-2

Vivian L. | Microsoft Word/Excel/Outlook, essay composition, math; I LOVE TO TEACHMicrosoft Word/Excel/Outlook, essay comp...
3.0 3.0 (1 lesson ratings) (1)
0
Hi Angelica;
-6x-6y=6
-6x+3y=-12
Let's subtract the second equation from the first...
-6x-(6x)=6x+6x=0
-6y-3y=-9y
6--12=6+12=18
0-9y=18
The x is eliminated...
-9y=18
Let's divide both sides by -9...
(-9y)/-9=18/-9
y=-2
Let's plug this into either equation to establish the value of x.
I randomly select the first equation...
-6x-6y=6
-6x-[(6)(-2)]=6
-6x-(-12)=6
Subtracting a negative number is identical to adding a positive number...
-6x+12=6
Let's subtract 12 from both sides...
-6x+12-12=6-12
-6x=-6
Let's divide both numbers by -6...
(-6x)/-6=-6/-6
x=1
Let plug both values into the second equation to verify...
-6x+3y=-12
[(-6)(1)]+[(3)(-2)]=-12
-6+-6=-12
-12=-12